2012
DOI: 10.1007/s00221-012-3231-4
|View full text |Cite
|
Sign up to set email alerts
|

Reference frames for coding touch location depend on the task

Abstract: The position of gaze (eye plus head position) relative to body is known to alter the perceived locations of sensory targets. This effect suggests that perceptual space is at least partially coded in a gaze-centered reference frame. However, the direction of the effects reported has not been consistent. Here, we investigate the cause of a discrepancy between reported directions of shift in tactile localization related to head position. We demonstrate that head eccentricity can cause errors in touch localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…For instance, the role of eye and head direction has been systematically investigated in a series of studies on tactile localization demonstrating that relevant body locations can be coded in external space according to several different reference points (Ho and Spence, 2007; Harrar and Harris, 2009; Pritchett and Harris, 2011; Pritchett et al, 2012; Mueller and Fiehler, 2014). When participants were asked to localize the position of a tactile stimulus presented to the participants’ body, the presence of systematic eye-position and head-position related errors revealed that not only the eye but also the head position contributed to the representation of external space (Ho and Spence, 2007; Harrar and Harris, 2009; Pritchett and Harris, 2011; Pritchett et al, 2012). In addition, also the body midline might be used as a reference point to code tactile locations under specific circumstances (Pritchett et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the role of eye and head direction has been systematically investigated in a series of studies on tactile localization demonstrating that relevant body locations can be coded in external space according to several different reference points (Ho and Spence, 2007; Harrar and Harris, 2009; Pritchett and Harris, 2011; Pritchett et al, 2012; Mueller and Fiehler, 2014). When participants were asked to localize the position of a tactile stimulus presented to the participants’ body, the presence of systematic eye-position and head-position related errors revealed that not only the eye but also the head position contributed to the representation of external space (Ho and Spence, 2007; Harrar and Harris, 2009; Pritchett and Harris, 2011; Pritchett et al, 2012). In addition, also the body midline might be used as a reference point to code tactile locations under specific circumstances (Pritchett et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…When participants were asked to localize the position of a tactile stimulus presented to the participants’ body, the presence of systematic eye-position and head-position related errors revealed that not only the eye but also the head position contributed to the representation of external space (Ho and Spence, 2007; Harrar and Harris, 2009; Pritchett and Harris, 2011; Pritchett et al, 2012). In addition, also the body midline might be used as a reference point to code tactile locations under specific circumstances (Pritchett et al, 2012). These results suggest the existence of multiple reference points for external representations of body locations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, visual and external reference frames seem to be weighted more strongly when the task comprises a motor action (Pritchett et al, 2012;Gherri and Forster, 2012;Fiehler, 2014a, 2014b), or when non-informative vision is provided (Newport et al, 2002). Furthermore, remapping effects were larger when a tactile task explicitly required remapping (for example, when the external location of touch was relevant for the response), than when the task was based on anatomical touch location (for example, reporting the stimulated finger, Gallace et al, 2008).…”
Section: Introductionmentioning
confidence: 92%
“…The effect appears to be equally affected by either eye or head displacement and is therefore best described as relating to gaze, the sum of eye and head position (Pritchett and Harris, 2011). The perceived location of touch also depends on whether a participant moves their gaze between the presentation of the touch and reporting its perceived location (Pritchett et al, 2012; Mueller and Fiehler, 2014). The perceived location shifts in the same direction as gaze if a gaze change occurs before the report (Harrar and Harris, 2009; Pritchett and Harris, 2011; Harrar et al, 2013), but in the opposite direction if the person does not move before making their report (Ho and Spence, 2007; Pritchett et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…If participants shift gaze before reporting, displacements are in the direction of gaze (C) . Data redrawn from Pritchett et al (2012).…”
Section: Introductionmentioning
confidence: 99%